Problematika Pembelajaran Agama Islam dalam Membina Akhlak Siswa Kelas VII SMP Swasta Utama Medan - Pebi Nurmala; Abdul Fattah Nasution; Ihsan Satrya Azhar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research was conducted at SMP Swasta Utama Medan. This research aims to describe (1) The process of learning Islamic religious education at SMP Swasta Utama Medan; (2) Problems of learning Islamic religion at SMP Swasta Utama Medan; (3) Efforts made to overcome the problems of learning Islamic religion at SMP Swasta Utama Medan. This type of research is qualitative with a Phenomenology method approach. Data collection for this research was carried out using the methods; (1) Observation (2) Interview; (3) Documentation. The data that has been collected is processed through data reduction, data presentation and drawing conclusions. The subjects used in this study were Islamic religious education teachers at SMP Swasta Utama Medan. The objects of this research were students of class VII of SMP Swasta Utama Medan. The results of this study indicate that; (1) The process of learning Islamic religious education at SMP Swasta Utama Medan is still not running well. (2) The problems that occur in Islamic religious education learning at SMP Swasta Utama Medan are: lack of interest and motivation of students, students are less disciplined, and students' manners (morals) are still not good. The problems that occur with teachers are the lack of competence in controlling the class and the lack of competence in mastering the learning material. (3) Efforts made are to create a conducive learning atmosphere, reprimand and advise students so that interest and motivation are created in students, provide grades and praise so that students are motivated, give punishments to students who are not disciplined, and reflect on the heart so that students are aware of their mistakes. The religious habituation activities that have been carried out at SMP Swasta Utama Medan are also quite good things to implement, because they are felt to bring positive things to students in fostering noble morals.